AN ANALYSIS ON STUDENT'S DIFFICULTIES IN READING COMPREHENSION AT SMKN 1 BANGKINANG - Rianti, Wida; Masdelima, Masdelima; Armiati, Armiati; Alifunnas, Muhammad; Nabila, Indah; Jannah, Miftahul; Ayu, Resky (Universitas Islam Lamongan, 2023)
This research is related to student's difficulties in reading comprehension. The purpose of this study is to determine the student's difficulties in reading. This research is descriptive. The population of this research is the second-semester students of class XI of SMKN 1 Bangkinang. The sample consist of 24 students. This research was conducted using a questionnaire. The finding of the study showed that the student had difficulty long sentence and text, vocabulary, grammar, knowing the background, and concentration are the main problem faced by students class XI of SMKN 1 Bangkinang